1993
DOI: 10.1002/yea.320090602
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIV‐1 nef in yeast: The 27 kDa nef protein is myristylated and fractionates with the nucleus

Abstract: The nef gene of human immunodeficiency virus type 1 (HIV-1) has been expressed in the yeast Saccharomyces cerevisiae to produce native Nef proteins. The proteins of M(r) 27 kDa and 25 kDa, produced by translation from the first and second start codons of the nef gene react with human HIV-1 antisera. Under low-level steady-state expression conditions, Nef27 undergoes myristylation and is targeted to the nuclear fraction while Nef25 is not myristylated and not nuclear localized. When produced rapidly and to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Therefore, the observation in the present study that extracellular soluble Nef induced apoptosis in MVECs is consistent with the bystander effect hypothesis (27), which implicates a viral protein or virally stimulated cellular factors released into the medium as mediators of apoptosis (24,72). Since Nef is synthesized early during initial viral infection and it has been shown that Nef produced by recombinant plasmids is secreted into culture medium (31,50,61), it is possible that intracellular expression of Nef in this study resulted in the release of the protein into the culture, which in turn may have caused the bystander effects. Hence, it could also be said that the induction of apoptosis in MVECs by intracellular Nef is also consistent with the bystander effect hypothesis (27).…”
supporting
confidence: 72%
“…Therefore, the observation in the present study that extracellular soluble Nef induced apoptosis in MVECs is consistent with the bystander effect hypothesis (27), which implicates a viral protein or virally stimulated cellular factors released into the medium as mediators of apoptosis (24,72). Since Nef is synthesized early during initial viral infection and it has been shown that Nef produced by recombinant plasmids is secreted into culture medium (31,50,61), it is possible that intracellular expression of Nef in this study resulted in the release of the protein into the culture, which in turn may have caused the bystander effects. Hence, it could also be said that the induction of apoptosis in MVECs by intracellular Nef is also consistent with the bystander effect hypothesis (27).…”
supporting
confidence: 72%
“…Detailed immunohistochemical and subcellular fractionation studies have shown that, while Nef is predominantly plasma membrane localized, significant amounts of Nef protein are also found in the cytoplasm and nucleus (27,32,40,41,43). Similarly, MDM-2 localizes to the nucleus and cytoplasm (4).…”
Section: Discussionmentioning
confidence: 99%
“…In infected cells Nef localizes at the plasma membrane and preferentially associates with the cytoskeleton, but it is also found in the cytoplasm, at the nuclear membrane, and in the nucleus (27,32,40,41,43). Three key functions of Nef, which are potentially interrelated, may explain its contribution to disease.…”
mentioning
confidence: 99%
“…The HIV-1 genomic clone pNL4-3 (23) was the source of HIV-1 genes that were amplified by polymerase chain reaction (PCR). The cloning of vpu and nef has been described (24,25). The cloning of vpr is described in Fig.…”
mentioning
confidence: 99%